Validating the performance of direct fastening (PAF) into concrete with high-speed measuring technology - Scholz, Ronja; Franck, Pascal; Yousef, Alhussain; Spyridis, Panagiotis; Walther, Frank (Technische Universität Dortmund, 2023)
In recent years, attention has been driven to the direct fastening technology by use of power actuated nail-type fasteners (PAFs) set in concrete. By means of the series of tests shown in this paper and the high-speed measuring equipment used, a first approach to the possibility of evaluating the setting performance is demonstrated. The difficulty is to judge whether the operation was successful and whether the fastening can bear the required force, since it is not possible to look into the concrete. For example, it remains hidden whether and, if so, how much the nail was deflected and bent by the concrete. Furthermore, it is unknown how the surrounding concrete was affected by occurring strains and heating as a result of friction. Since the setting process is very fast, it is necessary to use high-speed measurement technology. In the case of the studies conducted, both digital image correlation (DIC) and thermography were used to record material responses. Following the setting process, the nails and the surrounding concrete were separated and examined with computer tomography (CT). The CT provides the information on the inside of the concrete and one can see cracks and other reactions to the setting process.
ce/papers; 6(5)
Keywords: Direct fastening (nail-type); power actuated fasteners (PAF); fastening systems; high speed testing; setting process; digital image correlation; thermography; 660; Nagelverbindung; Beton; Abbinden; Bildkorrelation; Computertomografie; Thermografie